Phase I study of salazosulfapyridine in combination with cisplatin and pemetrexed for advanced non‐small‐cell lung cancer. Issue 9 (26th July 2017) - Otsubo, Kohei; Nosaki, Kaname; Imamura, Chiyo K.; Ogata, Hiroaki; Fujita, Akitaka; Sakata, Shinya; Hirai, Fumihiko; Toyokawa, Gouji; Iwama, Eiji; Harada, Taishi; Seto, Takashi; Takenoyama, Mitsuhiro; et al.
Abstract : Spliced variant isoforms of CD44 (CD44v) are a marker of cancer stem cells in solid tumors. They stabilize the xCT subunit of the transporter system xc(–) and thereby promote synthesis of the antioxidant glutathione. Salazosulfapyridine (SASP) is an inhibitor of xCT and suppresses the proliferation of CD44v‐positive cancer cells. Chemotherapy‐naïve patients with advanced non‐squamous non‐small‐cell lung cancer were enrolled in a dose‐escalation study (standard 3 + 3 design) of SASP in combination with cisplatin and pemetrexed. The primary end‐point was the percentage of patients who experience dose‐limiting toxicity. Fifteen patients were enrolled in the study. Dose‐limiting toxicity was observed in one of six patients at a SASP dose of 1.5 g/day (elevation of aspartate and alanine aminotransferase levels, each of grade 3), two of five patients at 3 g/day (hypotension or pneumonitis, each of grade 3), and two of three patients at 4.5 g/day (anorexia of grade 3). The maximum tolerated dose was thus 3 g/day, and the recommended dose was 1.5 g/day. The overall response rate was 26.7% and median progression‐free survival was 11.7 months, much longer than that for cisplatin–pemetrexed alone in previous studies. Exposure to SASP varied markedly among individuals according to ABCG2 and NAT2 genotypes. The serum concentration of free CD44v protein was increased after the first cycle of treatment, possibly reflecting death of cancer stem cells. Salazosulfapyridine was thus given safely in combination with cisplatin–pemetrexed, with the addition of SASP tending to prolong progression‐free survival. This trial is registered in the UMIN Clinical Trials Registry as UMIN000017854. Abstract : Salazosulfapyridine (SASP) has been reported to suppress the proliferation of CD44v‐positive cancer stem cells. In this phase I study, SASP was administered safely in combination with cisplatin‐pemetrexed, with the addition of SASP tending to prolong progression‐free survival.